ANALISIS PENGARUH PENDAPATAN PERKAPITA, CADANGAN DEVISA, NILAI TUKAR UANG DAN HARGA MINYAK MENTAH DUNIA TERHADAP VOLUME IMPOR MIGAS DI INDONESIA TAHUN 1993-2022 - Citrawana, Mochamad Dika; Septiani, Yustirania; Hutajulu, Dinar Melani (SINERGI : Jurnal Riset Ilmiah, 2025)
The abstract is a brief summary of the entire article’s contents. The Indonesia is a country rich in natural resources, including oil and natural gas. However, in recent decades, Indonesia's dependence on oil and gas imports has continued to increase. This is due to a decline in domestic oil and gas production, which can no longer meet the growing national energy demand. This demand is driven not only by population growth but also by economic growth, which has led to increased energy consumption year after year. As a country that still relies heavily on crude oil and gas imports, Indonesia faces significant challenges in maintaining trade balance and economic stability. The purpose of this study is to determine and analyze the effect of Per Capita Income, Foreign Exchange Reserves, Exchange Rate, and World Crude Oil Prices on the Volume of Oil and Gas Imports in Indonesia from 1993 to 2022. This research uses time series data from 1993 to 2022 sourced from the World Bank and Statistics Indonesia (BPS). The study employs multiple linear regression analysis using the Ordinary Least Squares (OLS) method, processed with EViews 10 software. The results indicate that Per Capita Income and Foreign Exchange Reserves do not have a significant effect on the Volume of Oil and Gas Imports in Indonesia during the 1993–2022 period. In contrast, the Exchange Rate and World Crude Oil Prices have a significant effect on the Volume of Oil and Gas Imports.